2022
DOI: 10.1108/ijrdm-11-2021-0535
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of augmented reality in online impulse behaviour

Abstract: PurposeThis study aims to examine the role of augmented reality (AR) in online impulse behaviour for highbody-involvement products. This study further explores whether flow and spatial presence mediate the link between AR and online impulse behaviour.Design/methodology/approachThe authors collected 255 responses from shopping mall visitors and used SPSS (21.0) (PROCESS macro) and AMOS 21.0 to test the hypothesised model.FindingsThe findings reveal that AR virtual try-on significantly influences online impulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 74 publications
(193 reference statements)
0
35
0
Order By: Relevance
“…, 2017). On the other hand, some researchers argued that AR being an interactive tool, is used primarily to derive hedonic value (Kumar and Srivastava, 2022; Hsu et al. , 2021; Nikhashemi et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…, 2017). On the other hand, some researchers argued that AR being an interactive tool, is used primarily to derive hedonic value (Kumar and Srivastava, 2022; Hsu et al. , 2021; Nikhashemi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature on AR marketing uncovers several dimensions such as AR media characteristics and consumer response (Javornik, 2016), consumer acceptance of AR (McLean and Wilson, 2019; Huang and Liao, 2015), customer experience (Huang et al. , 2019) and AR's impact on consumer behavior (Kumar, 2021; Kumar and Srivastava, 2022). Additionally, an in-depth review of existing literature on AR marketing reveals that scholars have shown keen interest in investigating how various media characteristics such as interactivity, augmentation, vividness and novelty (McLean and Wilson, 2019; Javornik, 2016; Yim et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations